In vitro and in vivo antioxidant and toxicity evaluation of different fractions of oxalis corniculata linn - Alam, M. Badrul; Hossain, M. Sarowar; Chowdhury, Nargis Sultana; Mazumder, M. Ehsanul Haque; Haque, M. Ekramul; Islam, Anwarul (© 2011 Academeic Journals Inc., 2016)
This article was published in Journal of Pharmacology and Toxicology [© 2011 Academeic Journals Inc.] and the definite version is available at: http://docsdrive.com/pdfs/academicjournals/jpt/2011/337-348.pdf